Phase separation glass

The phase separation glass formed by spinodal decomposition and acid treatment solves the problem that it is difficult to realize low-loss insulating materials under high-frequency signals in the prior art, and achieves the low dielectric constant and loss effect required for high-frequency electronic equipment.

JP2025511284APending Publication Date: 2025-04-15CORNING INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024558254
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-04-01
Filing Date
2023-03-27
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The prior art is difficult to provide low loss insulating materials at high signal frequencies, especially above 10 GHz, and these materials may have cracks or excessive fluidity during molding, limiting their application in certain molding methods.

Method used

The phase separation glass formed by spinodal decomposition is first extended into glass sheets, and then treated in an acidic solution to remove part of the phases to form high-purity SiO2 glass, and cured by heating to achieve a low dielectric constant and loss effect.

Benefits of technology

A glass material with extremely low dielectric constant and loss at high signal frequency is realized, and the material is not prone to cracks during the molding process, and is suitable for high-frequency electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025511284000001_ABST
    Figure 2025511284000001_ABST
Patent Text Reader

Abstract

A method of making a glass article using a phase separated silicate glass comprising a silica-rich first phase and a boron-rich second phase. The phase separated silica glass is etched with an etchant to remove at least a portion of the second phase to obtain a porous glass article with high silica content. The porous glass article can be heat treated to solidify the porous glass article to close the pores of the porous glass article and obtain a solidified glass article with extremely low dielectric properties. A variety of glass compositions are disclosed that phase separate by spinodal decomposition.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of priority under 35 U.S.C. § 119 to U.S. Provisional Application No. 63 / 326,308, filed April 1, 2022, the contents of which are relied upon and incorporated by reference in their entirety herein. The present disclosure generally relates to phase-separated glasses having at least two distinct glass phases. The phase-separated glasses disclosed herein can be fusion formed and further processed to provide glass articles with extremely low dielectric constants and loss tangents. [Background technology]

[0002] Digital technology continues to expand, especially in terms of data connection and processing speeds, for example from processing speeds of around 1 gigabit / s to speeds of around tens of gigabits / s. To achieve these data rates, the corresponding electronic device technologies often result in an expansion of signal transmission and reception frequencies from around 1 GHz to around 10 GHz, and in some cases even up to around 100 GHz. As these signal frequencies increase to accommodate increased data processing speeds, the technical specifications and requirements regarding absorption losses associated with the insulating materials used in these devices become more important. Although there are materials available that have low loss tangents at frequencies above 10 GHz, the processing characteristics of these materials may limit their ability to be produced using certain molding methods. There are commercially available materials that are used as insulating layers in PCBs. For example, one common glass epoxy laminate used as an insulating layer in PCB applications has a loss tangent of 0.0058 at a signal frequency of 10 GHz. However, as the industry moves to higher and higher signal frequencies, this insulating laminate has limited loss tangent. Other laminates, such as fused silica / polymer laminates, have been found that exhibit low loss properties at frequencies above 10 GHz. However, the mechanical properties of the fused silica and polymer layers limit the use of these laminates in some processes, as the fused silica layer can crack during post-processing. Materials such as Radome pyroceramics, high purity fused silica, sapphire, alumina, and silica can have low loss tangents at frequencies above 10 GHz. However, these materials may have high viscosities at forming temperatures that may limit their ability to be processed using standard sheet forming methods, such as slot draw and overflow downdraw. There are also alkali-free glass and glass-ceramic materials that have low loss tangents at frequencies above 10 GHz, examples of which include the B2O3-P2O5-SiO2 ternary (BPS) system and the MgO-Al2O3-SiO2 (MAS) system. However, these systems typically have liquidus viscosities that are too low for common forming methods. Summary of the Invention

[0003] A method of making a glass article is disclosed that includes forming a molten glass, the molten glass undergoing spinodal decomposition to produce a phase-separated molten glass comprising a first phase, a second phase, and a total SiO2 content ranging from about 59 mol% to about 69 mol% and a B2O3 content ranging from about 9 mol% to about 20 mol%, drawing the phase-separated molten glass into a glass sheet, and exposing the glass sheet to a first acid solution at a temperature ranging from about 60°C to about 95°C for a time ranging from about 16 hours to about 24 hours to remove at least a portion of the second phase from the glass sheet and obtain a porous glass sheet comprising a total silica content greater than about 95 mol%, the first acid solution comprising about 5% to about 40% by weight of an inorganic or organic acid. For example, the first acid solution can comprise at least one of HCl, H2SO4, HNO3, HF, or H3PO4. In an aspect, the first acid solution can comprise at least one of citric acid or acetic acid.

[0004] The calculated open porosity of the porous glass sheet may be greater than about 28%. In some embodiments, the first acid solution can include HCl, for example, about 5% HCl by weight. The method can include heat treating the porous glass sheet at a temperature ranging from about 500° C. to about 700° C. for a time ranging from about 45 minutes to about 75 minutes. In an embodiment, the method includes heating the porous glass sheet to a temperature in the range of about 900° C. to about 1100° C. for a time in the range of about 1 hour to about 24 hours to consolidate the porous glass sheet to obtain a consolidated glass sheet, the consolidated glass sheet having a dielectric constant D of less than about 4.0 measured at 10 GHz using a split post dielectric resonator. k The method may include steps including: In an embodiment, the solidified glass sheet D k may be less than about 3.5. In embodiments, the consolidated glass sheet has a loss tangent D of less than about 0.0075, measured at 10 GHz using a split post dielectric resonator. f may include. In some embodiments, the consolidation temperature is about 1000° C. or higher, and the consolidated glass sheet has a loss tangent D of less than about 0.003, measured at 10 GHz using a split post dielectric resonator. f In some embodiments, D f may be less than about 0.001, measured at 10 GHz using a split post dielectric resonator. The method may further comprise exposing the porous glass sheet to a second acid solution comprising HF for a time period between 1 minute and 15 minutes prior to the heat treating step. In aspects, drawing the molten glass into a glass sheet can include flowing the molten glass as separate streams of molten glass across converging shaped surfaces of a forming body, where the separate streams of molten glass meet along a lower end of the forming body. In some aspects, the drawing can include flowing the molten glass from a slot located at a lower portion of the vessel.

[0005] In an aspect, a glass article is described comprising a spinodally decomposed glass comprising a first phase and a second phase, the glass comprising, on an oxide basis, about 57 mol % to about 70 mol % SiO, about 4.7 mol % to about 10.5 mol % AlO, about 11.2 mol % to about 15.2 mol % BO, about 1.2 mol % to about 7.4 mol % ZnO, and about 3.7 mol % to about 20 mol % total of one or more alkaline earth oxides (RO), where the RO is selected from MgO, CaO, SrO, and BaO. The glass may include about 0.09 mol % to about 0.15 mol % SnO. In embodiments, the glass can include about 1.5 mol % to about 9.6 mol % MgO. In an embodiment, MgO / ZnO may be from about 0 to about 3.7. In an embodiment, B2O3 / ZnO may be from about 1.6 to about 12.6. Dielectric constant of glass D k may be about 4.5 to about 6.3. Loss tangent of glass Df may be about 0.002 to about 0.005. In an embodiment, the glass article can include at least one of La2O3, Y2O3, or Li2O in an amount less than about 3.0 mol%. In an embodiment, the glass article can include about 0.05 mol % to about 4.8 mol % CaO.

[0006] In another aspect, a glass article is disclosed comprising a spinodally decomposed glass comprising a first phase and a second phase, the glass comprising, on an oxide basis, about 59 mol% to about 69 mol% SiO, about 3 mol% to about 13 mol% AlO, about 9.8 mol% to about 20 mol% BO, and about 3.9 mol% to about 11.5 mol% total of one or more alkaline earth oxides (RO), where the RO are selected from MgO, CaO, SrO, and BaO. In an embodiment, the B2O3 / (Al2O3+SiO2) of the glass may be about 0.12 to about 0.3. In an embodiment, the glass can include SiO2 in the range of about 68.0 mol % to about 69.0 mol %.

[0007] Dielectric constant of glass D k may be about 4.7 to about 5.4. Loss tangent of glass D f may be about 0.002 to about 0.004. In yet another aspect, a glass sheet is described comprising greater than 95 mol% SiO, less than 1 mol% AlO, less than about 3 mol% BO, and less than about 0.5 mol% total alkaline earth oxides (RO), where RO is selected from MgO, CaO, SrO, and BaO.

[0008] The glass sheet can include a width greater than about 340 mm and a length greater than about 440 mm, for example, a width greater than about 680 mm and a length greater than about 880 mm, or a width greater than about 1500 mm and a length greater than about 1800 mm. In some embodiments, the glass sheet has a loss tangent D of less than about 0.005, measured at 10 GHz using a split post dielectric resonator. f For example, a loss tangent D of less than about 0.004, less than about 0.003, less than about 0.002, or less than about 0.001, measured at 10 GHz. f The glass sheet may include a dielectric constant of less than about 4.0, measured at 10 GHz using a split post dielectric resonator. In an embodiment, the glass sheet may be a porous glass sheet with an open porosity of greater than 28%.The pores of the porous glass sheet with a diameter of greater than 3 nm may comprise less than about 8.7% of the total pores of the glass sheet, as measured by mercury intrusion.The median d50 pore size of the pores of the porous glass sheet may be less than about 0.05 μm.

[0009] Additional features and advantages will be set forth in the following detailed description, and in part will become apparent to those skilled in the art from that description, or may be learned by practicing the embodiments described herein, including the following detailed description, the claims, and the accompanying drawings. It is understood that both the foregoing general description and the following detailed description are merely exemplary and are intended to provide an overview or framework for understanding the nature and characteristics of the claims. The accompanying drawings are included to provide a further understanding, and are incorporated in and constitute a part of this specification. The drawings illustrate one or more embodiments, and together with the description, serve to explain the principles and operation of the various embodiments. [Brief description of the drawings]

[0010] [Figure 1] 1 is a schematic diagram of an exemplary fusion downdraw glass production apparatus. [Diagram 2] 1 is a photograph of an exemplary phase separated glass according to the present disclosure. [Diagram 3] 1 is a plot depicting X-ray diffraction (XRD) data confirming that there is no crystallization in the glass and that the phase separation is between the two glass phases. [Figure 4]1 is a plot showing optical transmission as a function of wavelength for two glasses, a commercially available non-phase separated glass (Corning Eagle XG), and an exemplary phase separated glass. [Diagram 5] 5 is a plot showing reflectance between the Corning Eagle XG of FIG. 4 and an exemplary phase-separated glass as a function of wavelength. [Figure 6] 5A is a strain scope image of an as-drawn sample of the exemplary phase-separated glass of FIG. 4 and (b) an SEM image of the exemplary phase-separated glass. [Figure 7] 5A is a strain scope image of the exemplary phase-separated glass sample of FIG. 4 after heat treatment at 720° C. for 2 hours, and (b) an SEM image of the exemplary phase-separated glass after heat treatment. [Figure 8] 8A is a strain scope image of the exemplary phase-separated glass sample of FIG. 7 after a second heat treatment at 720° C. for 2 hours, and (b) an SEM image of the same exemplary phase-separated glass sample after a second heat treatment. [Figure 9] 5 is an SEM image of the exemplary phase-separated glass sample of FIG. 4 after heat treatment at 745° C. for 24 hours. [Figure 10] 5 is an SEM image of the exemplary phase-separated glass sample of FIG. 4 after heat treatment at 800° C. for 24 hours. [Figure 11] 5 is an SEM image of the exemplary phase-separated glass sample of FIG. 4 after heat treatment at 850° C. for 24 hours. [Figure 12] 5 is an SEM image of the exemplary phase-separated glass sample of FIG. 4 after heat treatment at 900° C. for 24 hours. [Figure 13] 1 is a schematic diagram of the coordinate system used to evaluate the Fourier transform of data from a phase separated glass. [Figure 14] FIG. 1 shows the corresponding two-dimensional Fourier transform (2DFT) of the sample measured from the x-surface. [Figure 15] 1 shows Fourier transform data for three surfaces of an exemplary phase-separated glass sample plotted in the rθ coordinate system, (a) represents the x-section, (b) represents the y-section, and (c) represents the z-section. [Figure 16] 17 is a plot showing corner stresses for the glass sheet of FIG. 16 as the glass composition transitions from a commercial glass (Corning Eagle XG) to an exemplary phase-separated glass during the production process, showing a gradual increase in stress over the transition period. [Figure 17] 17 is a schematic diagram of a glass sheet showing points along an edge portion of the glass sheet where the stress measurements of FIG. 16 were taken. [Figure 18] 1 is a plot showing the loss tangent as a function of time exhibited by glasses formed from a commercial non-phase separated glass composition to an exemplary phase separated glass composition, showing a gradual decrease in loss tangent. [Figure 19] 1 is a plot showing stress in a glass sheet produced from a glass melt as a function of time when the (B2O3+MgO) / CaO ratio (calculated in wt %) of the glass melt is changed during the transition from a commercial non-phase separated glass composition to an exemplary phase separated glass composition. [Figure 20] 1 is a plot of dielectric constant as a function of replacement of MgO with ZnO for exemplary phase-separated glasses. [Figure 21] 21 is a plot of loss tangent as a function of replacement of MgO with ZnO for the exemplary phase-separated glass of FIG. [Figure 22] 1 is a plot of dielectric constant as a function of replacement of MgO with ZnO for an exemplary phase-separated glass, and as a function of total RO (or R2O) in an exemplary phase-separated glass, including ZnO replacing B2O3. [Diagram 23] 23 is a plot of loss tangent as a function of replacement of MgO with ZnO for the exemplary phase-separated glass of FIG. 22 as a function of total RO (or R2O) in the exemplary phase-separated glass, including Zn replacing B2O3. [Figure 24] 1 is a plot of resistivity as a function of temperature (° C.) for the resistivity of GS57 and GS17. [Diagram 25]1 is a plot of dielectric constant as a function of La2O3 mole % when La2O3 is substituted for BaO in glass composition GS72. [Figure 26] 1 is a plot of loss tangent as a function of La2O3 mole % when La2O3 is substituted for Ba in glass composition GS72. [Figure 27] 1 is a plot of dielectric constant as a function of La2O3 mole % or Y2O3 mole % when added to a Sr—Ba-containing aluminoborosilicate glass. [Figure 28] 1 is a plot of loss tangent as a function of La2O3 mole % or Y2O3 mole % when added to a Sr—Ba-containing aluminoborosilicate glass. [Figure 29] 1 is a plot of Dk at 10 GHz as a function of transition metal oxide mole % when added as a replacement for CaO in glass composition GS17. [Diagram 30] 1 is a plot of D at 10 GHz as a function of transition metal oxide mole % when added as a replacement for CaO in glass composition GS17. [Diagram 31] FIG. 1 is a plot of Dk at 10 GHz as a function of F-mol% when added as a replacement for B2O3. [Diagram 32] FIG. 1 is a plot of D at 10 GHz as a function of F-mol % when added as a replacement for B2O3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] In the following detailed description, example embodiments disclosing specific details are shown for purposes of explanation, not limitation, to provide a thorough understanding of the various principles of the present disclosure. However, it will be apparent to one of ordinary skill in the art having the benefit of this disclosure that the present disclosure may be practiced in other embodiments that depart from the specific details disclosed herein. Moreover, descriptions of well-known devices, methods, and materials may be omitted so as not to obscure the description of the various principles of the present disclosure. Finally, where applicable, like reference numerals refer to like elements.

[0012] Ranges can be expressed herein as from "about" one particular value, and / or to "about" another particular value. When such a range is expressed, another embodiment includes from the one particular value and / or to the other particular value. Similarly, when values ​​are expressed as approximations, by use of the antecedent "about," it will be understood that the particular value forms another embodiment. It will be further understood that each of the endpoints of a range is significant in relation to the other endpoint, and independently of the other endpoint.

[0013] Unless otherwise indicated, all compositions are expressed in terms of as-weighed (i.e., component content) mole percent (mol%). As will be understood by those skilled in the art, various melting components (e.g., fluorine, alkali metals, boron, etc.) may undergo different levels of volatilization (e.g., as a function of vapor pressure, melting time, and / or melting temperature) during melting of the components. Thus, the term "about" with respect to such components is intended to encompass values ​​within about 1 mol% when measuring the final article compared to the as-weighed composition shown herein. With this in mind, substantial compositional equivalence between the final article and the as-weighed composition is expected. Unless expressly indicated otherwise, no method set forth herein should be construed as requiring that its steps be performed in a particular order. Thus, unless a method claim actually recites the order in which its steps follow, or unless the claims or specification expressly state that the steps are limited to a particular order, no order is intended to be inferred in any respect. This holds true for any possible non-expressive basis for interpretation, including logical events regarding the arrangement or operational flow of steps, obvious meanings derived from grammatical constructions or punctuation, and / or the number or type of embodiments described herein.

[0014] Concentrations of components (e.g., SiO2, Al2O3, etc.) of the glass compositions described herein are given in mole percent (mol %) on an oxide basis unless otherwise indicated. A variety of processes can be used to form the glass articles described herein, including, but not limited to, fusion, slot draw, and float glass processes. As used herein, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to a "component" includes embodiments having two or more such components, unless the context clearly dictates otherwise. As used herein, the term "CTE" refers to the coefficient of thermal expansion of glass materials, elements, and the like in this disclosure averaged over the temperature range of about 20° C. to about 300° C., unless otherwise indicated.

[0015] The term "dielectric constant (D k )" refers to the dielectric constant of a glass structure, design, or article of the present disclosure. The term "loss tangent" in this disclosure refers to the inherent dissipation of electromagnetic energy (e.g., heat) provided by a particular glass, layer, or laminate structure associated with an embodiment of this disclosure. The lower the dielectric loss (e.g., the portion of energy lost as heat), the more efficient the dielectric material. The loss tangent may be parameterized in terms of either the loss angle δ or the corresponding loss tangent tan δ. Permittivity is the ability of a material, such as the glasses of this disclosure, to store electrical energy in the presence of an external electric field. Additionally, the terms "permittivity" and "dielectric constant (D k The terms "dielectric constant" and "dielectric constant (D)" are used interchangeably in this disclosure. Dielectric constant is a measure of a material's ability to store electrical energy in an electric field. Dielectric constant is a complex quantity because it describes the phase and magnitude of polarization associated with an oscillating magnetic field. k ) and "Relative Dielectric Constant (ε r ) are used interchangeably in this disclosure and are defined as the ratio between the real part of the complex permittivity (absolute permittivity) and the permittivity of free space (vacuum permittivity). ε rMaterials with a dielectric constant >1 are dielectric materials and are considered poor conductors of electricity. Materials with low dielectric constants can withstand stronger electrostatic fields without experiencing dielectric breakdown. Dielectric breakdown, in most solid materials, results in the material conducting electrical current, which can lead to damage to the material. "Loss tangent" is expressed as the ratio of the imaginary and real parts of the complex dielectric constant. In general, the dielectric constant and loss tangent of a material depend on the frequency of the external field. Therefore, dielectric properties measured in the kHz range may not represent the dielectric properties at microwave frequencies. Furthermore, unless otherwise stated, the "loss tangent" and "dielectric constant (D k The "measurement method" attribute may be measured at frequencies above 1 GHz using a split post dielectric resonator (SPDR) or open cavity resonator configuration according to techniques understood by those of ordinary skill in the art of the present disclosure. The particular method selected may be selected based on the thickness of the sample and its lateral dimensions.

[0016] As used herein, molten glass refers to a molten material formed by heating batch materials in a melting vessel, which, when cooled, is capable of forming glass. "Molten glass" has a viscosity in the range of about 1 kpoise to about 200 kpoise.

[0017] As used herein, spinodal decomposition refers to a phase transformation in which a material, e.g., a glass material, having a single thermodynamic phase, separates, e.g., spontaneously, into multiple, coexisting but separate phases, e.g., two phases without nucleation. The separate phases can be dispersed throughout the glass, e.g., entangled. The separate phases can be present in approximately equal proportions and occupy approximately equal volumes. Thus, the term "phase-separated glass" as used herein refers to a glass that undergoes spinodal decomposition to result in a glass having at least two stable, entangled phases, with the interconnected second phase dispersed throughout the interconnected first phase. One phase (e.g., the first or major phase) may be rich in a first chemical species (e.g., SiO2) and the second (e.g., minor) phase may be rich in a second chemical species (e.g., B2O3). That is, the first phase may, for example, predominantly comprise all SiO2 and the second phase predominantly comprise all B2O3.

[0018] As used herein, solidification (e.g., solidifying) refers to a process in which a porous material is subjected to heating conditions suitable to bring the material to at least its softening temperature, e.g., melting point, whereby the pores of the porous material close and the material becomes non-porous and becomes a solid article, e.g., a solid glass article, that does not contain pores distributed throughout. For example, the heating conditions may be a temperature above the glass transition temperature, Tg, of the material.

[0019] The glasses and glass articles of the present disclosure may be suitable for electronic devices, electronic device substrates, and other equivalent applications that allow higher frequency communication of devices without significant degradation in performance as it relates to other non-electronic device requirements. For example, as higher frequency communication signals are used in these devices, the signals must pass through various physical barriers that would otherwise attenuate or block these signals. Thus, the glasses and / or glass articles of the present disclosure may be well suited for use as these barriers. Examples of these physical barriers include electrically insulating substrates used in the fabrication of electronic circuits and signal transmission structures, device covers, and other related structures that may be used to house circuits and other electronic device components used in electronic devices that operate at high signal frequencies. In some embodiments, the glasses of the present disclosure may be suitable for use as substrates in printed circuit boards (PCBs). PCBs typically include an insulating layer laminated with a copper film. In some implementations, the glasses of the present disclosure may be characterized by low loss tangents and mechanical properties suitable for use as insulating layers in PCBs, optionally in combination with one or more polymeric substrate layers. The glasses of the present disclosure may be substantially free of alkali metals to reduce the possibility of ion migration during processing.

[0020] Some aspects of the present disclosure also relate to glass that has suitable properties for production, particularly for forming methods such as slot draw and overflow fusion draw. Fusion draw is an industrial technique that has been used for large-scale production of thin glass sheets, such as sheets having a thickness of less than about 3 mm, such as less than about 1 mm, less than about 0.7 mm, or even less than about 0.1 mm. Compared to other flat glass production techniques, such as float or slot draw, fusion draw produces thin glass sheets with a high degree of flatness and surface quality. As a result, fusion draw is often the primary production technique in the fabrication of thin glass substrates (e.g., for liquid crystal displays and for cover glass for various personal electronic devices).

[0021] 1 is an exemplary glass manufacturing apparatus 10. The glass manufacturing apparatus 10 comprises a glass melting furnace 12 that includes a melting vessel 14. In addition to the melting vessel 14, the glass melting furnace 12 may include one or more additional components, such as heating elements (e.g., combustion burners and / or electrodes), configured to heat the raw materials and convert the raw materials into molten material and then into molten glass. For example, the melting vessel 14 may be an electrically boosted melting vessel in which energy is added to the raw materials through both the combustion burners and by direct heating, and an electric current is passed through the raw materials, thereby adding energy via Joule heating of the raw materials. The glass melting furnace 12 may include other thermal management devices (e.g., thermal insulation components) that reduce heat loss from the melting vessel. The glass melting furnace 12 may include electronic and / or electromechanical devices that facilitate melting of the raw materials into a glass melt. The glass melting furnace 12 may include support structures (e.g., support housings, support members, etc.) or other components.

[0022] The melting vessel 14 can be formed from a refractory material, such as a refractory ceramic material including alumina or zirconia, although the refractory ceramic material can include other refractory materials, such as yttrium (e.g., yttria, yttria stabilized zirconia, yttrium phosphate), zircon (ZrSiO4) or alumina-zirconia-silica, or even chromium oxide, either used alternatively or in any combination. In some examples, the melting vessel 14 can be constructed from refractory ceramic brick. The glass melting furnace 12 can be incorporated as part of a glass manufacturing apparatus configured to fabricate glass articles, such as glass ribbons, but the glass manufacturing apparatus may also be configured to form other glass articles, such as, but not limited to, glass rods, glass tubes, glass envelopes (e.g., glass envelopes for lighting fixtures, such as light bulbs), and glass lenses. In some examples, the glass melting furnace 12 may be included in a glass manufacturing apparatus including a slot draw apparatus, a float bath apparatus, a downdraw apparatus (e.g., a fusion downdraw apparatus), an updraw apparatus, a pressing apparatus, a rotating apparatus, a tube drawing apparatus, or any other glass manufacturing apparatus that may provide advantages to the present disclosure. By way of example, FIG. 1 diagrammatically illustrates a glass melting furnace 12 that is part of a fusion downdraw glass manufacturing apparatus 10 for fusion drawing a glass ribbon into individual glass sheets for subsequent processing or for spinning a glass ribbon on a spool. As used herein, the step of fusion drawing includes flowing molten glass over sloping, e.g., converging, sides of a forming body, with the resulting streams of molten material joining and fusing at the bottom of the forming body to form a glass ribbon.

[0023] The glass manufacturing system 10 may include upstream glass manufacturing equipment 16 located upstream of the melting vessel 14. In some instances, a portion of the upstream glass manufacturing equipment 16 or the entire upstream glass manufacturing equipment 16 may be incorporated as part of the glassmelting furnace 12.

[0024] As shown in FIG. 1 , the upstream glass manufacturing equipment 16 may include a raw material reservoir 18, a raw material delivery device 20, and a motor 22 connected to the raw material delivery device 20. The raw material reservoir 18 may be configured to store raw materials 24 that may be fed to the melting vessel 14 of the glass melting furnace 12 through one or more feed ports, as indicated by arrow 26. The raw materials 24 typically include one or more glass-forming metal oxides and one or more modifiers. In some examples, the raw material delivery device 20 may be powered by the motor 22 to deliver a predetermined amount of the raw materials 24 from the raw material reservoir 18 to the melting vessel 14. In further examples, the motor 22 may power the raw material delivery device 20 to introduce the raw materials 24 at a controlled rate based on a level of molten glass sensed downstream from the melting vessel 14 relative to the flow direction of the molten glass. The raw materials 24 in the melting vessel 14 may then be heated to form molten glass 28. Typically, the raw materials are added to the melting vessel as particles, for example, as various "sands." The raw material 24 may also include scrap glass (i.e., cullet) from previous melting and / or forming operations. A combustion burner may be used to initiate the melting process. In an electrically boosted melting process, once the electrical resistance of the raw material is sufficiently reduced by the combustion burner, an electrical boost may be initiated by developing an electrical potential between electrodes positioned in contact with the raw material, thereby establishing an electrical current through the raw material, which typically enters a molten state.

[0025] The glass manufacturing system 10 may also include downstream glass manufacturing equipment 30 located downstream of the glassmelting furnace 12 relative to the flow direction of the molten glass 28. In some instances, a portion of the downstream glass manufacturing equipment 30 may be incorporated as part of the glassmelting furnace 12. For example, a first connecting conduit 32, described below, or other portions of the downstream glass manufacturing equipment 30 may be incorporated as part of the glassmelting furnace 12.

[0026] The downstream glass manufacturing apparatus 30 can include a first conditioning chamber, e.g., a fining vessel 34, located downstream from the melting vessel 14 and connected to the melting vessel 14 by the previously described first connecting conduit 32. In some instances, the molten glass 28 may be gravity fed from the melting vessel 14 to the fining vessel 34 by the first connecting conduit 32. The first connecting conduit 32 thus provides a flow path for the molten glass 28 from the melting vessel 14 to the fining vessel 34. However, other conditioning chambers may be located downstream of the melting vessel 14, e.g., between the melting vessel 14 and the fining vessel 34. In some embodiments, a conditioning chamber may be used between the melting vessel and the fining chamber. For example, the molten glass from the primary melting vessel may be further heated in a secondary melting (conditioning) vessel or may be cooled in the secondary melting vessel to a temperature lower than the temperature of the molten glass in the primary melting vessel before entering the fining chamber.

[0027] The gas bubbles can be removed from the molten glass 28 by a variety of techniques. For example, the raw material 24 can include a polyvalent compound (i.e., a fining agent), such as tin oxide, that undergoes a chemical reduction reaction to release oxygen when heated. Other suitable fining agents can include, but are not limited to, arsenic, antimony, iron, and / or cerium, although the use of arsenic and antimony may be discouraged in some applications for environmental reasons due to their toxicity. The fining vessel 34 is heated, for example, to a temperature higher than the melting vessel internal temperature, thereby heating the fining agent to a reaction temperature sufficient for chemical reduction. Oxygen produced by the temperature-induced chemical reduction of one or more fining agents contained in the molten glass can diffuse into the gas bubbles created during the melting process. The increasingly buoyant and enlarged gas bubbles rise to the free surface of the molten glass in the fining vessel and are then evacuated from the fining vessel, for example, through a vent tube in fluid communication with the air above the free surface.

[0028] The downstream glass manufacturing equipment 30 may further include other conditioning chambers, such as a mixing device 36, e.g., a stirring vessel, for mixing the molten glass flowing downstream from the fining vessel 34. The mixing device 36 may be used to provide a homogenous glass melt composition, thereby reducing chemical and / or thermal inhomogeneities that may be inherently present in the molten glass exiting the fining vessel. As shown, the fining vessel 34 may be coupled to the mixing device 36 by a second connecting conduit 38. Thus, the molten glass 28 may be gravity fed from the fining vessel 34 to the mixing device 36 through the second connecting conduit 38. Typically, the molten glass in the mixing device 36 includes a free (e.g., gas) volume extending between a free surface and the top of the mixing device. Although the mixing device 36 is shown downstream of the fining vessel 34 with respect to the flow direction of the molten glass 28, the mixing device 36 may be located upstream of the fining vessel 34 in other embodiments. The downstream glass manufacturing equipment 30 can include multiple mixing devices, for example, a mixing device upstream of the fining vessel 34 and a mixing device downstream of the fining vessel 34. If used, multiple mixing devices can be of the same design or can be of different designs. One or more of the vessels and / or conduits disclosed herein can include static mixing vanes positioned to further promote mixing and subsequent homogenization of the molten materials.

[0029] The downstream glass manufacturing apparatus 30 may further include other conditioning chambers, such as a delivery vessel 40 located downstream of the mixing device 36. The delivery vessel 40 may function as an accumulator and / or flow controller to provide a consistent flow of molten glass 28 to the forming body 42 via an exit conduit 44. The molten glass in the delivery vessel 40, in some embodiments, includes a free surface and a free volume extends upward from the free surface to the top of the delivery vessel. As shown, the mixing device 36 may be coupled to the delivery vessel 40 by a third connecting conduit 46, and the molten glass 28 may be gravity fed from the mixing device 36 to the delivery vessel 40 through the third connecting conduit 46.

[0030] The downstream glass manufacturing apparatus 30 may further comprise a forming apparatus 48 configured to form a glass article, e.g., a glass ribbon. Thus, the forming apparatus 48 may include a downdraw apparatus, e.g., an overflow downdraw (e.g., fusion) apparatus, with the outlet conduit 44 positioned to deliver molten glass 28 from the delivery vessel 40 to an inlet conduit 50 of the forming body 42. The forming body in a fusion downdraw glass manufacturing apparatus may include a trough 52 disposed on an upper surface of the forming body, and an opposed converging forming surface 54 converging in a draw direction 56 along a lower end (root) 58 of the forming body. Molten glass delivered to the forming body trough 52 by the delivery vessel 40, the outlet conduit 44, and the inlet conduit 50 overflows the walls of the trough 52 and descends along the converging forming surface 54 as a separate stream of molten glass. The separate streams of molten glass meet below and along the root 58 to produce a ribbon of molten glass that is drawn from the root 58 in the draw direction 56 by applying a downward tension to the molten glass ribbon, for example, by gravity and opposing counter-rotating pulling rolls 62. The applied downward tension and the temperature of the molten glass can be used to control the dimensions of the glass ribbon as the molten glass cools and the viscosity of the molten glass increases. Thus, the molten glass ribbon goes through a viscosity transition from a viscous state, to a viscoelastic state, to an elastic state, and acquires mechanical properties that provide the glass ribbon 60 with stable dimensional properties. The glass ribbon 60 can be stamped using a stamping device 66 and separated into shorter lengths, such as glass sheets 64.

[0031] The downstream glass manufacturing equipment 30 components, including any one or more of the combining conduit 32, combining conduit 38, combining conduit 46, fining vessel 34, mixing device 36, delivery vessel 40, outlet conduit 44, or inlet conduit 50, may be formed of a precious metal. Suitable precious metals include platinum group metals selected from the group consisting of platinum, iridium, rhodium, osmium, ruthenium, and palladium, or alloys thereof. For example, the downstream glass manufacturing equipment components may be formed of a platinum-rhodium alloy including about 70% to about 90% by weight platinum and about 10% to about 30% by weight rhodium.

[0032] To facilitate fusion draw processing, the glass desirably has a sufficiently high liquidus viscosity (i.e., the viscosity of the molten glass at the liquidus temperature). A high liquidus viscosity can facilitate forming of the glass by downdraw processes such as fusion forming. The liquidus viscosity of a fusion-formable glass may be greater than about 140 kPoise. Furthermore, the fusion draw process can function over a wide range of viscosities. The glass is typically delivered to the trough of the forming body at a viscosity corresponding to about 20,000-35,000 Poise and leaves the base of the forming body as a viscous ribbon at a viscosity corresponding to about 100,000 Poise or greater. The temperature corresponding to a viscosity of 35,000 Poise is often used as an indication of the temperature at which the glass should be delivered to the trough of the forming body for fusion draw. The glasses of the present disclosure can have a temperature that facilitates forming by a downdraw process, e.g., a temperature corresponding to a 35,000 poise temperature (referred to herein as the "35,000 poise temperature") greater than about 1250° C. Typically, a low 35,000 poise temperature is desired to minimize undesirable creep of the refractory material of the forming body over time.

[0033] The temperature corresponding to a 200 poise viscosity is often used as a guideline for the preferred melting point of a glass. In some implementations, the glasses of the present disclosure may be characterized by a high 200 poise temperature, also referred to as a poise melting point (also referred to herein as a "200 poise melting point") for ease of molding. Preferably, the difference between the 200 poise temperature and the 35,000 poise temperature is about 450°C or less, such as about 420°C or less, for example about 400°C or less.

[0034] The phase-separated glass of the present disclosure has a β-amino acid content of about 57 mol % to about 71 mol %, for example, about 59 mol % to about 68 mol %, about 59 mol % to about 67 mol %, about 59 mol % to about 66 mol %, about 59 mol % to about 65 mol %, about 59 mol % to about 64 mol %, about 59 mol % to about 63 mol %, about 59 mol % to about 62 mol %, about 59 mol % to about 61 mol %, about 59 mol % to about 6 The total amount of SiO2 may be in the range of 1 mol%, in the range of about 59 mol% to about 60 mol%, in the range of about 60 mol% to about 69 mol%, in the range of about 61 mol% to about 69 mol%, in the range of about 62 mol% to about 69 mol%, in the range of about 63 mol% to about 69 mol%, in the range of about 64 mol% to about 69 mol%, in the range of about 65 mol% to about 69 mol%, in the range of about 66 mol% to about 69 mol%, in the range of about 67 mol% to about 69 mol%, and in the range of about 68 mol% to about 69 mol%. In some embodiments, the glasses of the present disclosure have a ZnO content in the range of about 67 mol % to about 71 mol %, e.g., about 67.2 mol % to about 69 mol %, about 67.4 mol % to about 69 mol %, about 67.6 mol % to about 69 mol %, about 67.8 mol % to about 69 mol %, about 68.0 mol % to about 69 mol %, about 68.2 mol % to about 69 mol %, about 68.4 mol % to about 69 mol %, including all ranges and subranges therebetween. The total amount of SiO2 may range from about 68.6 mol% to about 69 mol%, from about 68.8 mol% to about 69 mol%, from about 67 mol% to about 68.6 mol%, from about 67 mol% to about 68.4 mol%, from about 67 mol% to about 68.2 mol%, from about 67 mol% to about 68.0 mol%, from about 67 mol% to about 67.8 mol%, from about 67 mol% to about 67.6 mol%, from about 67 mol% to about 67.4 mol%. As used herein, the term "total amount" in the context of phase-separated glass refers to the amount of a chemical species in the phase-separated glass, regardless of the location of the chemical species in any of the individual phases present in the glass. Thus, for example, the total amount of SiO2 in a phase-separated glass that includes two phases refers to the combined amount of SiO2 that may be present in both phases.

[0035] The phase-separated glass of the present disclosure has a fluorine-containing fluoride content in the range of about 3 mol % to about 13 mol %, for example, in the range of about 3 mol % to about 12 mol %, in the range of about 3 mol % to about 11 mol %, in the range of about 3 mol % to about 10 mol %, in the range of about 3 mol % to about 9 mol %, in the range of about 3 mol % to about 8 mol %, in the range of about 3 mol % to about 7 mol %, in the range of about 3 mol % to about 6 mol %, in the range of about 3 mol % to about 5 mol %, in the range of about 3 mol % to about 4 mol %, including all ranges and subranges therebetween. The total amount of Al2O3 may be in the range of about 4 mol% to about 13 mol%, about 5 mol% to about 13 mol%, about 6 mol% to about 13 mol%, about 7 mol% to about 13 mol%, about 8 mol% to about 13 mol%, about 8 mol% to about 13 mol%, about 9 mol% to about 13 mol%, about 10 mol% to about 13 mol%, about 11 mol% to about 13 mol%, or about 12 mol% to about 13 mol%. In some embodiments, the glasses of the present disclosure have a ZnO content of about 7.6 mol % to about 8.7 mol %, e.g., in the range of about 7.6 mol % to about 8.6 mol %, from about 7.6 mol % to about 8.5 mol %, from about 7.6 mol % to about 8.4 mol %, from about 7.6 mol % to about 8.3 mol %, from about 7.6 mol % to about 8.2 mol %, from about 7.6 mol % to about 8.1 mol %, from about 7.6 mol % to about 8.0 mol %, from about 7.6 mol % to about 7.9 mol %, from about 7.6 mol % to about 7.8 mol %, including all ranges and subranges therebetween. The total amount of Al2O3 may be in the range of about 7.7 mol%, about 7.7 mol% to about 8.7 mol%, about 7.8 mol% to about 8.7 mol%, about 7.8 mol% to about 8.7 mol%, about 7.9 mol% to about 8.7 mol%, about 8.0 mol% to about 8.7 mol%, about 8.1 mol% to about 8.7 mol%, about 8.2 mol% to about 8.7 mol%, about 8.3 mol% to about 8.7 mol%, about 8.4 mol% to about 8.7 mol%, about 8.5 mol% to about 8.7 mol%, or about 8.6 mol% to about 8.7 mol%.

[0036] The phase-separated glass of the present disclosure has a β-amino acid content in the range of about 9% to about 20% including all ranges and subranges therebetween, for example, about 10 mol% to about 20 mol%, about 11 mol% to about 20 mol%, about 12 mol% to about 20 mol%, about 13 mol% to about 20 mol%, about 14 mol% to about 20 mol%, about 15 mol% to about 20 mol%, about 16 mol% to about 20 mol%, about 17 mol% to about 20 mol%, about 28 mol% to about 20 mol%, and the like. The total amount of B2O3 may be in the range of about 19 mol% to about 20 mol%, about 19% to about 9 mol%, for example, in the range of about 18 mol% to about 9 mol%, about 17 mol% to about 9 mol%, about 16 mol% to about 9 mol%, about 15 mol% to about 9 mol%, about 14 mol% to about 9 mol%, about 13 mol% to about 9 mol%, about 12 mol% to about 9 mol%, about 11 mol% to about 9 mol%, or about 10 mol% to about 9 mol%. In some embodiments, the glasses of the present disclosure comprise about 11.9 mol % to about 14.1 mol %, e.g., about 11.9 mol % to about 13.8 mol %, about 11.9 mol % to about 13.6 mol %, about 11.9 mol % to about 13.4 mol %, about 11.9 mol % to about 13.2 mol %, about 11.9 mol % to about 13.0 mol %, about 11.9 mol % to about 12.8 mol %, about 11.9 mol % to about 12.6 mol %, about 11.9 mol % to about 12.4 mol %, about 11.9 mol % to about 12.2 mol %, about 12.0 mol %, including all ranges and subranges therebetween. The total amount of B2O3 may range from about 12.2 mol% to about 14.1 mol%, from about 12.3 mol% to about 14.1 mol%, from about 12.4 mol% to about 14.1 mol%, from about 12.5 mol% to about 14.1 mol%, from about 12.6 mol% to about 14.1 mol%, from about 12.8 mol% to about 14.1 mol%, from about 13.0 mol% to about 14.1 mol%, from about 13.2 mol% to about 14.1 mol%, from about 13.4 mol% to about 14.1 mol%, from about 13.6 mol% to about 14.1 mol%, from about 13.8 mol% to about 14.1 mol%.

[0037] Increasing the amount of SiO2 may decrease the dielectric constant and loss tangent of the glass at frequencies above 10 GHz, but increasing the amount of SiO2 may decrease the formability of the glass, especially the formability by the downdraw method. For example, when the amount of SiO2 is increased, the liquidus temperature of the glass may increase. Pure SiO2 has a low CTE and is incompatible with the downdraw method due to its high melting point. B2O3 is added to make the viscosity of the glass lower, which can lower the liquidus temperature and facilitate the forming of the glass, especially by the downdraw method. B2O3 can have the effect of lowering the liquidus temperature more rapidly than the viscosity, and thus improve the liquidus viscosity for forming by the downdraw method. Al2O3 can lower the liquidus temperature and therefore increase the liquidus viscosity. Thus, the amounts of SiO2, B2O3, and optionally Al2O3 may be selected to balance the desired dielectric properties and formability of the glass in accordance with the present disclosure.

[0038] In some embodiments of the present disclosure, the total amount of SiO2, B2O3, and Al2O3 in the glass may be selected such that the ratio of B2O3:(Al2O3+SiO2) is about 0.1 to about 0.3, for example, in the range of about 0.12 to about 0.3, about 0.14 to about 0.3, about 0.16 to about 0.3, about 0.18 to about 0.3, about 0.2 to about 0.3, about 0.22 to about 0.3, about 0.24 to about 0.3, about 0.26 to about 0.3, or about 0.28 to about 0.3, including all ranges and subranges therebetween. In some embodiments, the ratio of B2O3:(Al2O3+SiO2) may be in the range of about 0.16 to about 0.18, about 0.16 to about 0.17, or about 0.17 to about 0.18.

[0039] In some embodiments, the total amount of SiO2 and B2O3 may be selected such that the sum of SiO2 plus B2O3 is from about 77 mol% to about 84 mol%, for example, in the range of about 78 mol% to about 84 mol%, in the range of about 79 mol% to about 84 mol%, in the range of about 80 mol% to about 84 mol%, in the range of about 81 mol% to about 84 mol%, in the range of about 82 mol% to about 84 mol%, in the range of about 83 mol% to about 84 mol%, in the range of about 77 mol% to about 83 mol%, in the range of about 77 mol% to about 82 mol%, in the range of about 77 mol% to about 81 mol%, in the range of about 77 mol% to about 80 mol%, in the range of about 77 mol% to about 79 mol%, or in the range of about 77 mol% to about 78 mol%, including all ranges and subranges therebetween.

[0040] In some embodiments, the total amount of SiO, B2O3, and Al2O3 in the phase-separated glasses disclosed herein is about 85 mol% to about 93 mol% of the sum of SiO2 plus B2O3 plus Al2O3, such as, for example, in the range of about 86 mol% to about 93 mol%, in the range of about 87 mol% to about 93 mol%, in the range of about 88 mol% to about 93 mol%, in the range of about 89 mol% to about 93 mol%, in the range of about 90 mol% to about 93 mol%, inclusive of all ranges and subranges therebetween. %, from about 91 mol% to about 93 mol%, from about 92 mol% to about 93 mol%, from about 85 mol% to about 92 mol%, from about 85 mol% to about 91 mol%, from about 85 mol% to about 90 mol%, from about 85 mol% to about 89 mol%, from about 85 mol% to about 88 mol%, from about 85 mol% to about 88 mol%, from about 85 mol% to about 87 mol%, or from about 85 mol% to about 86 mol%. According to some embodiments, if present, the phase separated glass may include one or more alkaline earth oxides (RO), where RO is MgO, CaO, BaO, and / or SrO.

[0041] The phase-separated glass of the present disclosure has a β-amino acid content of about 4% to about 6%, for example, about 4 mol % to about 5.8 mol %, about 4 mol % to about 5.6 mol %, about 4 mol % to about 5.4 mol %, about 4 mol % to about 5.2 mol %, about 4 mol % to about 5 mol %, about 4 mol % to about 4.8 mol %, about 4 mol % to about 4.6 mol %, about 4 mol % to about 4 ... % to about 4.2 mol %, about 4.2 mol % to about 6 mol %, about 4.4 mol % to about 6 mol %, for example, about 4.6 mol % to about 6 mol %, about 4.8 mol % to about 6 mol %, about 5 mol % to about 6 mol %, about 5.2 mol % to about 6 mol %, about 5.4 mol % to about 6 mol %, about 5.6 mol % to about 6 mol %, or about 5.8 mol % to about 6 mol %.

[0042] The phase-separated glass of the present disclosure has a fluorine-containing fluoride content in the range of about 3 mol % to about 6 mol %, for example, about 3.2 mol % to about 6 mol %, about 3.4 mol % to about 6 mol %, about 3.6 mol % to about 6 mol %, about 3.8 mol % to about 6 mol %, about 4 mol % to about 6 mol %, about 4.2 mol % to about 6 mol %, about 4.4 mol % to about 6 mol %, about 4.6 mol % to about 6 mol %, about 4.8 mol % to about 6 mol %, about 5 mol % to about 6 mol %, about 5.2 mol % to about 6%, for example, about 5.4 mol % to about 6 mol %, about 5.6 mol % to about 6 mol %, about 5.8 mol % to about 6 mol %, including all ranges and subranges therebetween. The total amount of CaO may be in the range of about 6 mol%, about 3 mol% to about 5.8 mol%, about 3 mol% to about 5.6 mol%, about 3 mol% to about 5.4 mol%, about 3 mol% to about 5.2 mol%, about 3 mol% to about 5 mol%, about 3 mol% to about 4.8 mol%, about 3 mol% to about 4.6 mol%, about 3 mol% to about 4.4 mol%, about 3 mol% to about 4.4 mol%, about 3 mol% to about 4.2 mol%, about 3 mol% to about 4 mol%, about 3 mol% to about 3.8 mol%, about 3 mol% to about 3.6 mol%, about 3 mol% to about 3.4 mol%, or about 3 mol% to about 3.2 mol%.

[0043] The phase separated glass of the present disclosure has an oxidized glass having a carboxyl group content of less than about 0.2 mol%, for example, in the range of about 0% to about 0.2 mol%, for example, in the range of about 0.02 mol% to about 0.2 mol%, including all ranges and subranges therebetween, such as, for example, in the range of about 0.04 mol% to about 0.2 mol%, in the range of about 0.06 mol% to about 0.2 mol%, in the range of about 0.08 mol% to about 0.2 mol%, in the range of about 0.1 mol% to about 0.2 mol%, in the range of about 0.12 mol% to about 0.2 mol%, in the range of about 0.14 mol% to about 0.2 mol%, in the range of about 0.16 mol% % to about 0.2 mol%, from about 0.18 mol% to about 0.2 mol%, from about 0 mol% to about 0.18 mol%, from about 0 mol% to about 0.16 mol%, from about 0 mol% to about 0.14 mol%, from about 0 mol% to about 0.12 mol%, from about 0 mol% to about 0.1 mol%, from about 0 mol% to about 0.08 mol%, from about 0 mol% to about 0.06 mol%, from about 0 mol% to about 0.4 mol%, or from about 0 mol% to about 0.02 mol%.

[0044] The phase separated glass of the present disclosure has an aryl group content of less than about 1 mol%, e.g., in the range of about 0% to about 1 mol%, e.g., in the range of about 0.1 mol% to about 1 mol%, including all ranges and subranges therebetween, e.g., in the range of about 0.2 mol% to about 1 mol%, in the range of about 0.3 mol% to about 1 mol%, in the range of about 0.4 mol% to about 1 mol%, in the range of about 0.5 mol% to about 1 mol%, in the range of about 0.6 mol% to about 1 mol%, in the range of about 0.7 mol% to about 1 mol%, in the range of about 0.8 mol% to about 1 mol%, inclusive of all ranges and subranges therebetween. %, in the range of about 0.9 mol % to about 1 mol %, in the range of about 0 mol % to about 0.9 mol %, in the range of about 0 mol % to about 0.8 mol %, in the range of about 0 mol % to about 0.7 mol %, in the range of about 0 mol % to about 0.6 mol %, in the range of about 0 mol % to about 0.5 mol %, in the range of about 0 mol % to about 0.4 mol %, in the range of about 0 mol % to about 0.3 mol %, in the range of about 0 mol % to about 0.2 mol %, or in the range of about 0 mol % to about 0.1 mol %.

[0045] In some embodiments, the one or more alkaline earth oxides are in the range of about 4.6 mol% to about 14.2 mol%, for example, in the range of about 4.8 mol% to about 14.2 mol%, in the range of about 5 mol% to about 14.2 mol%, in the range of about 5.4 mol% to about 14.2 mol%, in the range of about 5.8 mol% to about 14.2 mol%, in the range of about 6.2 mol% to about 14.2 mol%, in the range of about 7.2 mol% to about 14.2 mol%, in the range of about 8.2 mol% to about 14.2 mol%, in the range of about 9.2 mol% to about 14.2 mol%, in the range of about 10.2 mol% to about 14.2 mol%, in the range of about 11.2 mol%, inclusive of all ranges and subranges therebetween. % to about 14.2 mol%, from about 12.2 mol% to about 14.2 mol%, from about 13.2 mol% to about 14.2 mol%, from about 4.6 mol% to about 13.6 mol%, from about 4.6 mol% to about 12.6 mol%, from about 4.6 mol% to about 11.6 mol%, from about 4.6 mol% to about 10.6 mol%, from about 4.6 mol% to about 9.6 mol%, from about 4.6 mol% to about 8.6 mol%, from about 4.6 mol% to about 7.6 mol%, from about 4.6 mol% to about 6.6 mol%, or from about 4.6 mol% to about 5.6 mol%.

[0046] According to some aspects of the present disclosure, the phase-separated glass can include MgO and at least one additional alkaline earth oxide (RO) selected from CaO, BaO, and SrO. In some examples, the combination of MgO and at least one additional RO can result in a glass having a lower dielectric constant and / or loss tangent compared to a glass containing MgO or another RO alone. In some embodiments, the total amount of MgO and the total amount of additional RO, in coordination with the total amount of Al2O3 present in the glass, as described above, may be adjusted to provide a RO 全 Ratio of Al2O3 to RO 全 :Al2O3) is selected to be greater than 1. RO greater than 1 全 By providing a glass having a ratio of Al2O3 to Al2O3, it may be easier to form a producible glass that can be drawn using conventional glass forming methods. In some embodiments, the total amount of MgO to RO全 Ratio of MgO:RO 全 ) may be in the range of about 0.3 to about 4.7, for example, in the range of about 0.3 to about 4.5, in the range of about 0.3 to about 0.4, in the range of about 0.3 to about 3.5, in the range of about 0.3 to about 3, in the range of about 0.3 to about 2.5, in the range of about 0.3 to about 2, in the range of about 0.5 to about 1.5, in the range of about 0.5 to about 4.7, in the range of about 1 to about 4.7, in the range of about 1.5 to about 4.7, in the range of about 2 to about 4.7, in the range of about 2.5 to about 4.7, in the range of about 3 to about 4.7, in the range of about 3.5 to about 4.7, or in the range of about 4 to about 4.7, including all ranges and subranges therebetween.

[0047] For a given phase-separated glass, a lower dielectric constant and / or loss tangent may be achieved in a glass sample by reducing the concentration of a single RO species present in the glass. 全 For concentration, similar RO 全 It is believed that reduced dielectric constant and / or loss tangent may be achieved in glass samples by combining MgO with at least one additional RO species, e.g., CaO, SrO, and / or BaO, as compared to glasses derived from precursor compositions having a concentration of MgO but containing only a single RO species. 全 In terms of concentration, glasses including combinations of MgO plus CaO, SrO, and / or BaO according to the present disclosure can have a lower dielectric constant than glasses including only a single RO species selected from MgO, CaO, SrO, or BaO. 全 With respect to concentration, glasses including combinations of MgO plus CaO, SrO, and / or BaO according to the present disclosure can have lower loss tangents than glasses including only a single RO species selected from CaO, SrO, or BaO. Without wishing to be bound by theory, it is believed that for glasses derived from precursor compositions having a single RO species, as the concentration of the single RO species decreases, the dielectric constant and loss tangent of the derived glass, measured using a 10 GHz signal, also decrease.

[0048] In some embodiments, the amount of alkaline earth oxides in the phase-separated glass may be selected in combination with other materials, such as B2O3 and optionally Al2O3, to provide a phase-separated glass with desired properties. For example, increasing the amount of alkaline earth oxides relative to SiO2 and Al2O3 can have the effect of lowering the viscosity of the glass melt, and can increase the melting point and forming temperature. Alkaline earth oxides can also increase the CTE and density of the glass, and can affect other properties such as the elastic modulus as well. Alkaline earth oxides can also lower the liquidus temperature. Thus, in some embodiments, the total amount of alkaline earth oxides, B2O3, and Al2O3, may be selected to balance the desired physical properties and formability of the glass in accordance with the present disclosure. The phase-separated glasses of the present disclosure may contain a total amount of ZnO that is less than about 2 mol%, for example, in the range of about 0 mol% to about 1.5 mol%, in the range of about 0 mol% to about 1 mol%, in the range of about 0 mol% to about 0.5 mol%, in the range of about 0.5 mol% to about 2 mol%, in the range of about 1 mol% to about 2 mol%, or in the range of about 1.5 mol% to about 2 mol%, including all ranges and subranges therebetween.

[0049] In some embodiments, the total amount of alkaline earth oxides, B2O3 and Al2O3, is the RO in the glass. 全 In some embodiments, the ratio of RO:(Al2O3+B2O3) may be selected to be about 0.2 to about 0.6. 全 The ratio of RO:(Al2O3+B2O3) is about 0.2 to about 0.6, about 0.2 to about 0.5, about 0.2 to about 0.4, about 0.3 to about 0.6, about 0.3 to about 0.5, about 0.3 to about 0.4, about 0.4 to about 0.6, about 0.4 to about 0.5, or about 0.5 to about 0.6. 全 The ratio of: (Al2O3 + B2O3) is about 0.2, about 0.24, about 0.25, about 0.28, about 0.29, about 0.3, about 0.32, about 0.35, about 0.36, about 0.4, about 0.5, about 0.55, about 0.58, about 0.6, or any ratio between these values.

[0050] The phase-separated glasses of the present disclosure may include one or more fining agents, such as, but not limited to, SnO2, Sb2O3, As2O3, and / or one or more halogen salts, including salts of fluorine, chlorine, or bromine. When one or more fining agents are present in the glass, the fining agents can be present in a total amount of less than about 1 mol%. In some embodiments, the clarifier is present in an amount of about 0.01 mol % to about 1 mol %, e.g., in the range of about 0.01 mol % to about 1 mol %, in the range of about 0.01 mol % to about 0.09 mol %, in the range of about 0.01 mol % to about 0.08 mol %, in the range of about 0.01 mol % to about 0.07 mol %, in the range of about 0.01 mol % to about 0.06 mol %, in the range of about 0.01 mol % to about 0.05 mol %, in the range of about 0.01 mol % to about 0.04 mol %, in the range of about 0.01 mol % to about 0.03 mol %, in the range of about 0.01 mol % to about 0.02 mol %. In some embodiments, the fining agent may be present in an amount ranging from about 0.01 mol % to about 0.5 mol %, from about 0.02 mol % to about 0.1 mol %, from about 0.02 mol % to about 0.01 mol %, from about 0.03 mol % to about 0.1 mol %, from about 0.04 mol % to about 0.1 mol %, from about 0.05 mol % to about 0.1 mol %, from about 0.06 mol % to about 0.1 mol %, from about 0.07 mol % to about 0.1 mol %, from about 0.08 mol % to about 0.1 mol %, from about 0.08 mol % to about 0.1 mol %, or from about 0.09 mol % to about 0.1 mol %. In other embodiments, however, the fining agent may be present in an amount ranging from about 0.01 mol % to about 0.5 mol %.

[0051] If the content of the fining agent in the phase-separated glass is too high, the fining agent may enter the glass structure and affect various glass properties. However, if the content of the fining agent is too low, the phase-separated glass may be difficult to mold. According to one embodiment of the present disclosure, SnO2 may be included as a fining agent in a total amount ranging from about 0 mol% to about 0.3 mol%. For example, SnO2 may be present in a total amount ranging from about 0 mol% to about 0.3 mol%, from about 0 mol% to about 0.2 mol%, from about 0 mol% to about 0.1 mol%, from about 0.05 mol% to about 0.3 mol%, from about 0.05 mol% to about 0.2 mol%, or from about 0.05 mol% to about 0.1 mol%. The phase separated glass may contain contaminants or unintentional additives, such as TiO2 or ZrO2. These additional materials, if present, are typically present in very low or trace total amounts, such as less than about 0.5 mol%, e.g., in the range of 0 to about 0.4 mol%, in the range of 0 to about 0.4 mol%, in the range of 0 to about 0.3 mol%, in the range of 0 to about 0.3 mol%, in the range of 0 to about 0.2 mol%, or in the range of 0 to about 0.1 mol%.

[0052] In some embodiments, the phase-separated glass of the present disclosure is substantially free of alkali metals. As used herein, the term "substantially free" is defined to mean that no more than trace amounts of material, in this case alkali metal oxides, are present in a total amount, for example, about 0.5 mol% or less, 0.4 mol% or less, 0.3 mol% or less, about 0.2 mol% or less, or about 0.1 mol% or less. Trace amounts of alkali metal oxides may be present due to contamination or limitations in production. As noted above, in some implementations, the glass of the present disclosure may be produced without the addition of alkali metals, such that the glass is substantially free of alkali metals, to reduce the possibility of ion migration during heat treatment of articles formed with the glass. Reducing or minimizing the possibility of ion migration may be advantageous in some applications, such as when the glass is used as a substrate for electronic devices where ion migration is undesirable.

[0053] In some embodiments, the phase-separated glass of the present disclosure can include at least one alkali metal oxide (RO), where RO is LiO, NaO, and / or KO. In some embodiments, the one or more alkali metal oxides can be present, individually or in a combined amount, from 0 mol% to about 1 mol%. In some embodiments, the one or more alkali metal oxides can be present, individually or in a combined amount, from 0 mol% to about 1 mol%, from 0 mol% to about 0.9 mol%, from 0 mol% to about 0.8 mol%, from 0 mol% to about 0.7 mol%, from 0 mol% to about 0.6 mol%. For example, Na2O can be present in a total amount of 0 mol% to about 0.05 mol%, 0 mol% to about 0.01 mol%, 0 mol% to about 0.005 mol%, 0 mol% to about 0.001 mol%, about 0.001 mol% to about 0.05 mol%, about 0.001 mol% to about 0.01 mol%, or about 0.001 mol% to about 0.005 mol%. In another example, KO can be present in a total amount of 0 mol% to about 2 mol%, 0 mol% to about 1 mol%, 0 mol% to about 0.5 mol%, about 0.1 mol% to about 2 mol%, about 0.1 mol% to about 1 mol%, about 0.1 mol% to about 0.5 mol%, about 0.5 mol% to about 2 mol%, or about 0.5 mol% to about 1 mol%.

[0054] In some embodiments, the phase-separated glass of the present disclosure has a dielectric constant D measured with a 10 GHz signal. k In some implementations, the phase separated glass may be characterized by a dielectric constant D measured with a 10 GHz signal of about 10 or less. k In some implementations, the phase-separated glass can have a dielectric constant D measured with a 10 GHz signal of about 6 or less, such as about 5 or less. k It may have a molecular weight of about 4.5 to about 6. In some embodiments, the phase separated glass of the present disclosure has a loss tangent D measured with a 10 GHz signal. fThe phase-separated glasses of the present disclosure may be characterized by a loss tangent of about 0.004 or less, as measured with a 10 GHz signal. For example, the phase-separated glasses of the present disclosure may be characterized by a loss tangent of about 0.003 or less, as measured with a 10 GHz signal. In some embodiments, the phase-separated glasses of the present disclosure may be characterized by a loss tangent of about 0.0029 to about 0.004, as measured with a 10 GHz signal. Unless otherwise indicated, the dielectric properties D k and D. f was measured on polished, as-prepared glass samples measuring 3'' x 3'' and less than 1 mm thick. Test frequencies ranged from 2.7 GHz to 50 GHz. Samples were tested using split post dielectric resonators at signal frequencies up to 10 GHz, or open cavity resonators at signal frequencies greater than 10 GHz. In each case, the dielectric constant and loss tangent were measured from the shift and broadening of the resonance peak.

[0055] The phase separated glass of the present disclosure may be suitable for use in PCB applications. PCB laminates typically include an insulating layer laminated to a copper film, for example, with the insulating layer disposed between the copper clad films. The insulating layer preferably has low dielectric loss, for example, less than 0.005 at 10 GHz, and sufficient mechanical strength and fracture toughness to allow handling and post-processing in a manufacturing environment. The insulating layer should also be able to withstand drilling without damage or fracturing, and may range in thickness from about 100 to 700 micrometers, depending on the application. Additionally, the insulating layer can withstand temperatures up to 260°C for 30 seconds while maintaining dimensional stability. This temperature is typically based on the temperature required for solder reflow in the post-processing of PCB boards. Solder paste is typically used to attach electrical components to their conductive contact pads. The assembly is then exposed to high temperatures (typically 260°C for 30 seconds) to reflow the solder and create a permanent solder joint. Therefore, the insulating layers of a PCB should preferably be low dielectric loss materials that are also able to withstand the solder reflow temperatures commonly used in PCB processing with little or no softening or dimensional change.

[0056] During the drawing process, where the phase separated glass is placed under tension, e.g., in a downdraw process, and drawn into a glass sheet, it has been observed that optical retardation can occur in the phase separated glass sheet, as evidenced by stress across the glass sheet as shown by strainscope measurements using polarized light. Annealing has been shown to increase the optical retardation. The longer the annealing time, the more the optical retardation can increase.

[0057] FIGS. 5, 6, and 7 illustrate (1) strain scope images (5(a), 6(a), and 7(a)) of an approximately 3 centimeter (cm) by 3 cm sample of the phase separated glass sheet and (2) photographs from a scanning electron microscope (SEM) (FIGS. 5(b), 6(b), and 7(b)) showing each phase of the glass sample. The sample in FIG. 5 is an as-drawn sample of the glass that is not subsequently annealed. The sample in FIG. 6 is the sample after being annealed at 720° C. for 2 hours. FIG. 7 illustrates the sample in FIG. 6 after a second annealing at 720° C. for an additional 2 hours (i.e., a total of 4 hours). The increased shading, particularly in the sample in FIG. 7(a) from the strain scope measurement, suggests increased optical retardation. Furthermore, when comparing the SEM images in FIGS. 5-7, an increase in the size of the second phase is evident when the sample is annealed.

[0058] 8-11 illustrate SEM photographs of samples of the phase separated glass composition of FIG. 5 after annealing at increasing temperatures. For example, the sample of FIG. 8 was annealed at a temperature of about 745° C. for a time length of about 12 hours. Features indicative of phase separation were extremely fine and difficult to visually discern. The sample of FIG. 9 was annealed at a temperature of about 800° C. for a time length of about 12 hours. Here, the two phases of glass, although still small, are visually distinct. The sample of FIG. 10 was annealed at a temperature of about 850° C. for a time length of about 12 hours. The separate phases are clearly visible. The sample of FIG. 11 was annealed at a temperature of about 900° C. for a time length of about 12 hours. As clearly demonstrated, the separated phases of the glass are easily discerned. Similar to the results of FIGS. 5, 6, and 7, the higher the annealing temperature, the greater the degree of phase separation, as evidenced by the growth of a second phase. The second phase in FIG. 8 is barely discernible, whereas in the image of FIG. 11 the second phase is clearly visible.

[0059] Images similar to those in Figures 8-11 were analyzed using a two-dimensional Fourier transform technique. The sample was etched at a series of varying etch times to highlight the spatial distribution of the two phases. Close inspection of the images revealed that the edges of the more slowly etched material phase were brighter than the more quickly etched phase, giving a signal from the SEM image related to the spatial orientation of the phases. Mathematically, the two-dimensional Fourier transform can be described using the following equation:

[0060]

number

[0061] SEM images can be described using the coordinate system illustrated in Figure 12. The draw direction (represented in the figure by arrow 56) extends along the y-axis (in the -y direction), the thickness of the glass sheet is in the z-direction, and the x-direction is orthogonal to the draw and thickness directions, respectively. If a surface perpendicular to the surface on which the sample is imaged is parallel to the x-direction, the sample is shown as an x-section image. The corresponding two-dimensional Fourier transform (2DFT) of the sample measured from the x-surface is shown in FIG. 14. The thin halo around the central dot is a circular ring whose width corresponds to the characteristic width of the phase-separated feature (i.e., second phase) shown in FIG. 11. Its uniformity in radius and width suggests that the structure is approximately isotropic for this 2D cross-section. However, it is somewhat easier to see the inhomogeneity when plotted on a diagram in rθ space rather than uv space. However,

[0062]

number

[0063] Unlike other glasses that have been processed post-forming, e.g., by heat treating the glass to induce phase separation, the phase separated glasses of the present disclosure are believed to phase separate by spontaneous spinodal decomposition while the molten glass flows downstream through the glass-making apparatus 30, e.g., as it traverses the various connecting conduits and vessels downstream of the melting vessel and vessel prior to the forming body. This notion is supported by the effect that drawing of the molten glass from the forming body has on the orientation of the phases; i.e., phase separation must have already occurred and the drawing tension must have affected the phase orientation.

[0064] FIG. 16 illustrates the stress of a fusion downdraw drawn glass ribbon as a function of time as the glass composition changes from a commercially available non-phase separating glass (i.e., Corning® Eagle™ XG®) to a phase separating glass composition. The transition occurred over a period of approximately one month. The transition was achieved by slowly changing the glass composition while attempting to maintain a stable glass density. Stress data was collected at the edges of the glass sheet (e.g., corners and sides, see FIG. 17). The data shows a gradual change in stress (pounds per square inch, psi) from virtually no change in stress at the beginning of the transition (e.g., about day 3, as might be expected from a commercially available glass), to stresses of over + / - 250 pounds per square inch (psi) at the completion of the transition, to stresses of as much as + / - 300 psi at day 45. FIG. 18 shows the loss tangent D as a function of time during the transition from Corning® Eagle™ XG® glass to a phase-separated glass at various locations on the glass sheet (see FIG. 16). f is the log of stress 10 1 is a graph showing the stress versus loss tangent (e.g., from about 0.0065 to about 0.0045) plotted against the stress (psi). The data shows both an increase in stress, which is responsible for the inherent birefringence, and a decrease in loss tangent (e.g., from about 0.0065 to about 0.0045). Figure 19 is a plot of the ratio of (B2O3+MgO) / CaO (where the individual components are expressed in mole %) along with stress (psi) during the transition at several locations on the sheet (see Figure 16), showing that the dielectric properties changed with the composition change.

[0065] The first glass phase of the phase separated glasses disclosed herein is rich in SiO2, while the second phase is rich in boron (e.g., B2O3). As noted above, the higher the amount of SiO2 in the phase separated glass, the better its dielectric properties (e.g., dielectric constant D k and loss tangent D f) becomes more favorable. That is, the dielectric constant and / or loss tangent can be reduced by increasing the amount of SiO2. However, increasing the amount of SiO2 in glass makes it more difficult to form the glass by traditional sheet forming means, such as fusion downdraw methods. On the other hand, since the main form of such electronic (e.g., dielectric) components in PCBs is on the order of thin sheets, mass production methods can advantageously result in cost savings. Thus, a method is described for modifying the composition of a phase-separated intermediate sheet of glass, in which the amount of SiO2 in the glass phase can be greatly increased after forming the glass sheet. Thus, mass production methods can be used to form intermediate glass sheets, where the intermediate glass sheets are further processed to produce glass articles with a SiO2-rich phase.

[0066] In accordance with the present disclosure, the phase-separated glass article can be etched with a suitable etchant to remove substantially all of the boron-rich minor phase, leaving a silica-rich porous glass article that includes a silica-rich major phase. In some embodiments, the porous glass article can then be heated to solidify the porous glass article into a silica-rich solid glass article, such as a glass sheet. Thus, methods are described that include a first step of forming a glass sheet that includes a phase separated glass that includes at least a first phase and a second phase, such as the phase separated glass described herein. The phase separated glass sheet can include a width greater than about 340 mm and a length greater than about 440 mm, a width greater than about 680 mm and a length greater than about 880 mm, or a width greater than about 1500 mm and a length greater than about 1500 mm, although smaller or larger dimensions are contemplated, for example, using a fusion downdraw process such as the fusion downdraw process described herein.

[0067] The phase-separated glass sheet may have a first phase rich in SiO2 and a second phase rich in B2O3. The phase-separated glass sheet may be cleaned prior to a subsequent step. For example, the phase-separated glass may be cleaned with a detergent. An ultrasonic bath may be used for cleaning. For example, the phase-separated glass may be cleaned by immersing the phase-separated glass in an ultrasonic bath containing an aqueous solution containing a detergent, e.g., 4% by weight of Semiclean, for a time period ranging from about 2 minutes to about 6 minutes, e.g., about 4 minutes.

[0068] In a second step, the phase-separated glass sheet may be exposed to an etchant, e.g., an acid suitable for etching the second phase from the glass sheet. The acid may be an aqueous solution containing an inorganic or organic acid. The acid may be present in an amount of about 5% to about 40% by weight depending on the acid selected and the amount of the second phase to be removed. Suitable inorganic acids may include at least one of HCl, H2SO4, HNO3, HF, or H3PO4. Exemplary organic acids may include citric acid and / or acetic acid. The etchant may be at a temperature ranging from about 60°C to about 100°C, with an exposure time ranging from about 1 hour to about 6 hours, e.g., from about 2 hours to about 4 hours. The strength of the acid solution and the temperature of the etchant will determine the suitable time for etching the second phase from the phase-separated glass sheet. Removal of the second phase from the phase-separated glass sheet produces a porous glass sheet that contains mostly or entirely a first (matrix) phase, e.g., a SiO2-rich phase. The calculated open porosity of the porous glass sheet may be greater than about 28%. Only about 8.7% of the pores have a diameter greater than about 3 nm, meaning that the majority of the pores were less than about 3 nm in diameter. The median (d50) pore size of the pores of the porous glass sheet may be less than about 1 μm, such as less than about 0.5 μm, less than about 0.1 μm, less than about 0.05 μm, less than about 0.025 μm, or less than about 0.02 μm. Direct porosity measurements were performed using mercury intrusion into the pores. However, this technique is limited to pore sizes greater than 3 nm. Therefore, porosity was also calculated based on density.

[0069] In an optional subsequent step after the etching process, the porous glass article resulting from the etching process may be rinsed with deionized water, for example 18 Mohm deionized water. The porous glass article obtained from the above etching process can find other uses besides electronic applications. For example, because the second phase is interconnected, the etching process leaves behind pores that can be very small (e.g., diameters less than about 100 nm, less than about 75 nm, less than about 50 nm, less than about 25 nm, or even less than about 3 nanometers) that can extend through the thickness of the porous glass sheet. Despite the porous structure of the porous glass sheet, the porous glass sheet remains transparent. The porous glass sheet can be used in a variety of applications, such as nanofiltration, reverse osmosis, and water treatment applications. The surfaces of the pores can be treated (e.g., coated) so that the porous article can be used in microreactor (e.g., nanoreactor) applications (where chemical reactions can be carried out on an extremely small scale). The pore surfaces can be coated with a catalyst. In some embodiments, the pores can be impregnated with nano-sized particles to provide additional functionality.

[0070] In a third step of the method, the porous glass article may be consolidated by heating the porous glass article to a suitable temperature above the glass transition temperature Tg of the glass. Consolidation of the porous glass sheet may stabilize the performance of the glass sheet by preventing absorption of water molecules into the pores. Since water is a highly polarized molecule, moisture in the glass may adversely affect the dielectric properties of the glass. In an embodiment, the porous glass article may be preheated to a temperature in the range of about 100°C to about 300°C for a time in the range of about 1 hour to about 2 hours to dry the porous glass article before consolidation. The dried porous glass article may be further heated to a temperature in the range of about 500°C to about 700°C, for example, in the range of about 550°C to about 650°C, to remove (burn out) any organic contaminants, such as carbon, that may be contaminated in the porous glass article. Contaminants may include oils from handling, or other environmental contaminants. The dried porous glass article may be heated for a time ranging from about 30 minutes to about 2 hours, and preferably for a time ranging from about 45 minutes to about 75 minutes.

[0071] To solidify the porous glass article, the porous glass article may be heated to a solidification temperature in the range of about 900°C to about 1100°C, including all ranges and subranges therebetween, such as about 920°C to about 1100°C, or about 940°C to about 1100°C, about 960°C to about 1100°C, about 980°C to about 1100°C, about 1000°C to about 1100°C, about 1020°C to about 1100°C, about 1040°C to about 1100°C, about 1060°C to about 1100°C, or about 1080°C to about 1100°C. The porous glass article may be heated to the consolidation temperature for a time ranging from about 1 hour to about 4 hours, although longer consolidation times are contemplated, such as from about 1 hour to about 24 hours, from about 1 hour to about 20 hours, from about 1 hour to about 16 hours, from about 1 hour to about 12 hours, or from about 1 hour to about 8 hours, including all ranges and subranges therebetween. When heated to the consolidation temperature, the pores in the porous glass article close and at least a portion of the glass, or the entire glass, becomes solid depending on the temperature selected and the amount of consolidation desired. SEM and time-of-flight (ToF) secondary ion mass spectrometry (SIMS) showed that the porous glass remaining after the etching process is composed primarily of SiO2 (see Table 2). Dielectric property measurements indicate that once the porous glass is consolidated, D k Value and D f It has been shown that the dielectric constants of high purity fused silica (HPFS) can be comparable to those of HPFS. However, unlike HPFS, phase-separated glasses can be drawn into large glass sheets, e.g., by the fusion downdraw process, etched, and then consolidated to produce high-silica glass sheets with HPFS-like dielectric properties.

[0072] Table 1 describes phase-separated glass samples (GS17, see Table 5) that were etched according to the etching process described above using an aqueous acid solution containing 5% by weight HCl. All samples were 2'' x 2'' coupons of GS17 (see Table 5) that were cleaned in a 4% solution of semi-clean detergent in an ultrasonic bath at 65°C for 2 minutes and then dried in an oven at 110°C for 1 hour (except for Experiment C, which was not dried). All etching was performed in a 5% by weight HCl solution at 95°C. For reference, the glass before etching was D k 4.6 and D f Table 1 lists the experimental designations (A-DD), the first heat treatment (1st HT) expressed as temperature (Tp, °C) / time (Tm, hr), the second heat treatment (2nd HT) expressed as temperature (Tp, °C) / time (Tm, hr), the first solidification (1st Con.) expressed as temperature (Tp, °C) / time (Tm, hr), the second solidification (2nd Con.) expressed as temperature (Tp, °C) / time (Tm, hr), the surface treatment with hydrofluoric acid (HF) expressed as "before heat treatment" (B) or "after the last solidification" (A), the environmental immersion in an 85 °C / 85% relative humidity environment expressed as time (hr), and the dielectric constant D k and loss tangent D f The dielectric constants and loss tangents were measured at 10 GHz except those marked with an asterisk. The dielectric properties marked with an asterisk were measured at 5 GHz (sample distortion prevented measurements at 10 GHz). Samples with an apostrophe (') after the dielectric property indicate that the sample was exposed to the laboratory environment (72°C, 20% RH) for approximately 24 hours before the dielectric properties were measured. Samples with a cross symbol (†) after the dielectric property were exposed to the laboratory environment for approximately 60 hours before the dielectric properties were measured.

[0073] The glass from experiment DD was measured for its dielectric properties a first time after solidification and a second time after the 85°C / 85% RH soak. The double dashed line indicates that a method step was not performed. Thus, as usual, the samples of experiments AC were etched prior to the measurement of their dielectric properties, but were not heat treated, solidified, HF treated, or exposed to an 85°C / 85% RH environment. The data shows that when comparing the glass samples of experiments AC to the glass sample of experiment D, which was, for example, simply heated to a temperature of 200°C for 1 hour after the etching process without the benefit of further heating, the dielectric properties D k and D. f The results show a clear reduction in dielectric properties. It is believed that this reduction in dielectric properties occurred as a result of the removal of moisture from the porous sample obtained after the etching treatment. Similarly, the dielectric properties of the glass sample of experiment E were further reduced by including a consolidation step in which the sample was subjected to a temperature of 820° C. for 1 hour. Similar results can be observed for other samples, where the addition of further heating, either by one or more heat treatment steps or by one or more consolidation steps, can result in a reduction in dielectric properties. The glass sample of experiment DD shows that the sample was subjected to a temperature of 820° C. for 1 hour after the etching treatment and consolidation (including the HF treatment of the porous glass article prior to consolidation), and the dielectric properties of the glass sample of experiment D were further reduced. k and D. f The D was measured once for 24 hours after the solidified glass article was exposed to an 85°C / 85%RH environment, and then a second measurement was taken after the solidified glass article was exposed to an 85°C / 85%RH environment for 24 hours. k and D. f The values ​​of are highly invariant, indicating stable dielectric properties even in the presence of moisture.

[0074] [Table 1]

[0075] Table 2 lists the before and after compositions of fusion-formed GS17 glass samples before and after etching in 5 wt. % HCl at 95° C. Compositional analysis was performed using ToF SIMS to accurately estimate the glass composition remaining after the HCl etching process. The analysis was performed on a 500 micrometer by 500 micrometer area across the entire thickness of the sample. The components of the before composition reflect the total amount (including both phases of the phase-separated glass sample). All component amounts are given in mole %. The data shows a large increase in the relative amount of SiO2 after most of the boron-rich second phase was removed from the sample, resulting in a nearly pure SiO2 sheet that would not be possible to form via the fusion downdraw process. There was no indication of a compositional gradient being present. It is expected that other phase-separated glass compositions described herein will yield similar results after etching.

[0076] [Table 2]

[0077] Tables 3-9 below set forth exemplary phase separated glasses according to the present disclosure in mole percent (mol%) calculated on an oxide basis from the as weighed glass (glass precursor composition from which the glass is derived). The glass samples were weighed and drawn as glass ribbons in a fusion draw manufacturing apparatus and separated into glass sheets having dimensions of 1500 millimeters (mm) by 1850 mm. Phase separation was determined by SEM. The glass sheets had a thickness of 0.7 mm.

[0078] [Table 3]

[0079] [Table 4]

[0080] [Table 5]

[0081] [Table 6]

[0082] [Table 7]

[0083] [Table 8]

[0084] [Table 9]

[0085] Low dielectric constant (D k ) and dielectric loss tangent (D f Several different oxides were investigated to obtain improved ZnO content and enhanced durability. Tables 10 and 11 show the composition and measured D for glasses with ZnO addition. k and D. f Figures 20 and 21 show the effect of replacing MgO with ZnO in GS17 on the D k and D. f 1 is a plot showing the effect of k increases with the addition of ZnO to MgO, and D f decreased with the addition of ZnO. However, when ZnO was added as a replacement for B2O3 in the glass, D k and D. f The properties of D did not appear to change. This is shown in Figures 22 and 23. In Figures 22 and 23, the open circles are glasses with ZnO replacing B2O3, and as shown, they overlap with the filled circles which are the same glasses without ZnO. k and D. fis affected by the B2O3 content but not at all by the ZnO content. These data suggest that ZnO can potentially improve the meltability of the glass by lowering the resistivity associated with the B2O3 content in these types of glasses, while also improving the D of the glass. f To further lower the D k and D. f ZnO is a good option to retain the resistivity of the glass melt of GS57 with approximately 4 mol % ZnO is shown in FIG. 24. It is clear that glass sample GS57 has a lower resistivity compared to glass sample GS17. Note that GS57 does not contain CaO, while GS17 contains approximately 5 mol % CaO. The lack of CaO in GS17 and the low resistivity indicate the effectiveness of ZnO in lowering the resistivity and thereby improving the solubility.

[0086] [Table 10]

[0087] [Table 11]

[0088] Rare earth oxides are the D f Table 12 shows the composition for several glasses made with the addition of La2O3 or Y2O3, as well as the D of those glasses measured at 10 GHz. k and D. f 25 and 26 provide data on D as a function of La2O3 mole % for glasses with Ba substituted for La. k and D. f The plots clearly show that when La2O3 is increased in glasses with reduced BaO, D k increases, D f However, when La2O3 or Y2O3 is added to the top of the glass composition (not substituted for any specific oxide), D kBoth D and Df are increased from those of the parent glass that did not contain rare earth elements. Figures 27 and 28 show that D for glasses containing La2O3 and Y2O3 k and D. f The data show an increase in both D and Y2O3 where rare earth oxides were added to the base glass composition (La2O3 and / or Y2O3 were not a replacement for another component). f It is suggested that, to lower β, the rare earth oxide should rather be added as a substitution for one of the more bulk alkaline earth oxides of the glass.

[0089] [Table 12]

[0090] Transition metals (e.g., Co, Mn, Ni, Cu) have relatively low polarizability compared to other metal oxides, which reduces the D k and D. f Tables 13 and 14 show the compositions of several glasses containing various transition metal oxide additions and the D measured at 10 GHz obtained for each of the glasses. k and D. f As shown in Figure 29, the data show that transition metals (except Co) do not significantly affect D in alkaline earth aluminoborosilicate glasses when substituting for CaO. k However, the data presented in Figure 30 suggest that transition metals may provide a means of reducing the D f Not only does it not lower the f This suggests that the transition metals may be used to color the glass, which may cause the transition metals to remain substantially constant or increase compared to the parent glass.

[0091] [Table 13]

[0092] [Table 14]

[0093] Fluorine is a halide element that has been used in glass melting to reduce the viscosity of the glass melt and to aid in fining the glass melt. Fluorine, when replacing B2O3, has the same D as the base glass. k While substantially maintaining D f Table 15 shows the results of three alkaline earth aluminoborosilicate glass compositions containing F-additions to B2O3 and the D k and D. f Figures 31 and 32 show the data for D as a function of F-mol% added as a replacement for B2O3. k and D. f The data are for glasses containing 4.5 mole % F instead of B2O3, D k remains essentially the same, while D f This clearly shows that the D of glass f Not only does F- help to lower the B2O3 content of the glass, it also helps to reduce melt defects such as silica agglomerates, lowers the viscosity of the glass melt, and makes the glass easier to melt since less energy is required to melt. F- can also help to reduce bubbles or seeds that result from insufficient fining of the glass.

[0094] [Table 15]

[0095] It will be apparent to those skilled in the art that various modifications and variations may be made to the embodiments of the present disclosure without departing from the spirit and scope of the present disclosure. Therefore, the present disclosure is intended to cover such modifications and variations within the scope of the appended claims and their equivalents.

Claims

1. 1. A method of making a glass article, comprising: forming a molten glass, the molten glass undergoing spinodal decomposition to form a first phase, a second phase, and a total SiO in the range of about 59 mol % to about 69 mol %. 2 Content and B in the range of about 9 mol% to about 20 mol% 2 O 3 producing a phase separated molten glass comprising the drawing the phase separated molten glass into a glass sheet; exposing the glass sheet to a first acid solution at a temperature between about 60° C. and about 95° C. for about 16 hours to about 24 hours to remove at least a portion of the second phase from the glass sheet and obtain a porous glass sheet having a total silica content greater than about 95 mole percent; A method comprising:

2. The method of claim 1 , wherein the porous glass sheet has an open porosity greater than about 28%.

3. The first acid solution is HCl, H 2 SO 4 , HNO 3 , HF, or H 3 P.O. 4 The method of claim 1, comprising about 5% to about 40% by weight of at least one of:

4. The method of claim 3 , wherein the first acid solution comprises HCl.

5. 5. The method of claim 4, wherein the first acid solution comprises about 5% by weight HCl.

6. 10. The method of claim 1, wherein the first acid solution comprises from about 5% to about 40% by weight of at least one of citric acid or acetic acid.

7. The method of claim 1 , further comprising heating the porous glass sheet to a temperature between about 500° C. and about 700° C. for about 45 minutes to about 75 minutes.

8. heating the porous glass sheet to a temperature between about 900° C. and about 1100° C. for about 1 hour to about 24 hours to consolidate the porous glass sheet and obtain a consolidated glass sheet, the consolidated glass sheet having a dielectric constant D of less than about 4.0 measured at 10 GHz using a split post dielectric resonator; k The method of claim 1 further comprising the steps of:

9. D k 9. The method of claim 8, wherein is less than about 3.5 measured at 10 GHz using said split post dielectric resonator.

10. The consolidated glass sheet has a loss tangent D of less than about 0.0075, measured at 10 GHz using the split post dielectric resonator. f The method of claim 8 , comprising:

11. The method of claim 8 , wherein the solidification temperature is about 1000° C. or greater.

12. The consolidated glass sheet has a loss tangent D of less than about 0.003, measured at 10 GHz using the split post dielectric resonator. f The method of claim 11 , comprising:

13. D f 13. The method of claim 12, wherein is less than about 0.001, measured at 10 GHz.

14. 10. The method of claim 1, further comprising exposing the porous glass sheet to a second acid solution containing HF for about 1 minute to about 15 minutes prior to the heat treating step.

15. 2. The method of claim 1 , wherein the step of drawing the molten glass into the glass sheet comprises flowing the molten glass as separate streams of molten glass across converging shaped surfaces of a forming body, the separate streams of molten glass meeting along a lower end of the forming body.

16. The method of claim 1 , wherein the step of drawing the molten glass into the glass sheet comprises flowing the molten glass from a slot located in a bottom portion of a vessel.

17. 13. A glass article made by the method of claim 1.

18. 9. A glass article made by the method of claim 8.

19. 1. A glass article comprising a spinodally decomposed glass comprising a first phase and a second phase, the glass comprising, on an oxide basis: About 57 mol % to about 70 mol % SiO 2 , About 4.7 mol % to about 10.5 mol % Al 2 O 3 , About 11.2 mol % to about 15.2 mol % B 2 O 3 , about 1.2 mol % to about 7.4 mol % ZnO, and 1. A glass article comprising about 3.7 mol% to about 20 mol% combined of one or more alkaline earth oxides (RO), wherein RO is selected from MgO, CaO, SrO, and BaO.

20. 20. The glass article of claim 19, wherein the glass comprises from about 0.09 mol% to about 0.15 mol% SnO.

21. 20. The glass article of claim 19, wherein the glass comprises from about 1.5 mol% to about 9.6 mol% MgO.

22. 22. The glass article of claim 21, wherein MgO / ZnO is from about 0 to about 3.

7.

23. B 2 O 3 22. The glass article of claim 21, wherein ZnO is from about 1.6 to about 12.

6.

24. The dielectric constant D of the glass k 20. The glass article of claim 19, wherein the R is from about 4.5 to about 6.3 measured at 10 GHz using a split post dielectric resonator.

25. Loss tangent D of the glass f is about 0.002 to about 0.005 measured at 10 GHz using the split post dielectric resonator.

26. La 2 O 3 , Y 2 O 3 , or Li 2 20. The glass article of claim 19, further comprising at least one of O in an amount less than about 3.0 mol%.

27. 20. The glass article of claim 19, further comprising about 0.05 mol% to about 4.8 mol% CaO.

28. 1. A glass article comprising a spinodally decomposed glass comprising a first phase and a second phase, the glass comprising, on an oxide basis: About 59 mol % to about 69 mol % SiO 2 , About 3 mol % to about 13 mol % Al 2 O 3 , About 9.8 mol % to about 20 mol % B 2 O 3 , and 1. A glass article comprising about 3.9 mol% to about 11.5 mol% combined of one or more alkaline earth oxides (RO), wherein the RO are selected from MgO, CaO, SrO, and BaO.

29. B 2 O 3 / (Al 2 O 3 +SiO 2 29. The glass article of claim 28, wherein the σ is from about 0.12 to about 0.

3.

30. The glass has a SiO content in the range of about 68.0 mol % to about 69.0 mol %. 2 29. The glass article of claim 28, comprising:

31. The dielectric constant D of the glass k is about 4.7 to about 5.4 measured at 10 GHz using a split post dielectric resonator.

32. Loss tangent D of the glass f is about 0.002 to about 0.004 measured at 10 GHz using the split post dielectric resonator.

33. More than 95 mol% SiO 2 , Less than 1 mol% Al 2 O 3 , Less than about 3 mol % B 2 O 3 , 1. A glass sheet comprising less than 0.5 mol % in total of one or more alkaline earth oxides (RO), the RO being selected from MgO, CaO, SrO, and BaO.

34. 34. The glass sheet of claim 33, wherein the glass sheet comprises a width greater than about 340 mm and a length greater than about 440 mm.

35. 35. The glass sheet of claim 34, wherein the width is greater than about 680 mm and the length is greater than about 880 mm.

36. 36. The glass sheet of claim 35, wherein the width is greater than about 1500 mm and the length is greater than about 1800 mm.

37. 34. The glass sheet of claim 33, wherein the glass sheet is a porous glass sheet having an open porosity greater than 28%.

38. 38. The glass sheet of claim 37, wherein the pores in the porous glass sheet have a diameter greater than 3 nm, less than about 8.7% of the total pores as measured by mercury intrusion.

39. 38. The glass sheet of claim 37, wherein the median d50 pore size of the pores in the porous glass sheet is less than about 0.05 μm.

40. The glass sheet has a loss tangent D of less than about 0.003, measured at 10 GHz using a split post dielectric resonator. f 34. The method of claim 33, comprising:

41. D f 41. The method of claim 40, wherein is less than about 0.001 measured at 10 GHz using the split post dielectric resonator.

42. 1. A glass article comprising a spinodally decomposed glass comprising a first phase and a second phase, the glass comprising, on an oxide basis: 68.65 mol% SiO 2 , 7.61 mol% Al 2 O 3 , 14.65 mol% B 2 O 3 , and CaO in the range of about 1.3 mol % to about 4.4 mol %; and CuO, NiO, Co in amounts of 1 mol% to 4 mol% 3 O 4 , and MnO 2 A transition metal selected from Glass articles, including

43. The dielectric constant D of the glass k 43. The glass article of claim 42, wherein the R is in the range of about 4.4 to about 4.9, measured at 10 GHz using a split post dielectric resonator.

44. Loss tangent D of the glass f 44. The glass article of claim 43, wherein the R is in the range of about 0.0024 to about 0.005 measured at 10 GHz using the split post dielectric resonator.